MAN IN CONTEMPORARY SOCIETY: ALIENATION AND ANOMIE - Davies, Harold (Universidad Autónoma de Nuevo León, 2021)
THE CENTRAL THEME of the topic here developed involves the philosophical prospects of the day, or general trends in social thought and ideologies, the human condition of man including the question of man as a historical being, and something of the conditions of human life in the world today. These general questions lead us to the persistent and pervasive problem that the modern world confronts, the problem of widespread alienation, its frustrations and anxieties, together with the anomie of the present generation its tendency to reject the authority of all institutions and value systems of the past. Finally, I shall consider the pathways of the mind and spirit, creativity and social goodwill, as they relate to man's place in the world.